Learn more about

Refine search

Results (displaying matches 1-50 of 3911) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
713.a.713.1 713.a \(y^2 + (x^3 + x + 1)y = -x^5 - x\) $\mathrm{USp}(4)$ 1
743.a.743.1 743.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^2\) $\mathrm{USp}(4)$ 1
893.a.893.1 893.a \(y^2 + (x^3 + x + 1)y = -x^4 - x^2\) $\mathrm{USp}(4)$ 1
953.a.953.1 953.a \(y^2 + (x^3 + x + 1)y = x^3 + x^2\) $\mathrm{USp}(4)$ 1
968.a.1936.1 968.a \(y^2 + y = x^6 - x^4\) $G_{3,3}$ 1
1077.a.1077.2 1077.a \(y^2 + (x^3 + 1)y = x^4 + x^3 + 2x^2 + x\) $\mathrm{USp}(4)$ 1
1116.a.214272.1 1116.a \(y^2 + (x^3 + 1)y = x^4 + 2x^3 + x^2 - x\) $\mathrm{USp}(4)$ 0
1127.a.1127.1 1127.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^3 - x^2 - x\) $\mathrm{USp}(4)$ 1
1343.a.1343.1 1343.a \(y^2 + (x^3 + x + 1)y = x^5 - 2x^4 - x\) $\mathrm{USp}(4)$ 1
1343.b.1343.1 1343.b \(y^2 + (x^3 + x + 1)y = -3x^4 + x^3 + 2x^2 + x\) $\mathrm{USp}(4)$ 1
1468.a.2936.1 1468.a \(y^2 + (x^3 + x + 1)y = -x^5 - x^2\) $\mathrm{USp}(4)$ 1
1544.a.3088.1 1544.a \(y^2 + (x^3 + x^2 + x + 1)y = x^2\) $\mathrm{USp}(4)$ 1
1549.a.1549.1 1549.a \(y^2 + (x^3 + x + 1)y = -x^5 + x^3 - 3x\) $\mathrm{USp}(4)$ 1
1568.b.12544.1 1568.b \(y^2 + (x^3 + x)y = -x^4 + 1\) $G_{3,3}$ 1
1575.a.23625.1 1575.a \(y^2 + (x^3 + 1)y = x^5 - x^4 - 6x^3 + 2x^2 + 7x - 4\) $\mathrm{USp}(4)$ 1
1612.a.3224.1 1612.a \(y^2 + (x^3 + x + 1)y = x^3 + 2x^2 + x\) $\mathrm{USp}(4)$ 1
1721.a.1721.1 1721.a \(y^2 + (x^3 + 1)y = x^2 - x\) $\mathrm{USp}(4)$ 1
1844.a.3688.1 1844.a \(y^2 + (x^3 + x^2 + 1)y = x^4 + x^3 - x^2 - x\) $\mathrm{USp}(4)$ 1
1863.b.1863.1 1863.b \(y^2 + (x^3 + x + 1)y = -x^6 + x^4 - x^2 - x\) $\mathrm{USp}(4)$ 1
1900.a.3800.1 1900.a \(y^2 + (x^3 + x + 1)y = x^3 - x\) $\mathrm{USp}(4)$ 1
1915.a.1915.1 1915.a \(y^2 + (x^3 + x + 1)y = x^6 - 2x^4 - x\) $\mathrm{USp}(4)$ 1
1929.a.52083.1 1929.a \(y^2 + (x^2 + x + 1)y = 9x^5 + 6x^3 + 7x^2 + 2x\) $\mathrm{USp}(4)$ 1
2036.a.8144.1 2036.a \(y^2 + (x + 1)y = x^6 - 2x^5 + x^3\) $\mathrm{USp}(4)$ 1
2054.a.4108.1 2054.a \(y^2 + (x + 1)y = x^5 + 2x^4 - x^3 - 2x^2\) $\mathrm{USp}(4)$ 1
2060.a.4120.1 2060.a \(y^2 + (x^3 + x + 1)y = -x^5 + x^4 - x^2 - x\) $\mathrm{USp}(4)$ 1
2094.a.12564.1 2094.a \(y^2 + (x + 1)y = x^5 - 2x^4 - x^3 + 2x^2\) $\mathrm{USp}(4)$ 1
2156.b.34496.1 2156.b \(y^2 + (x^2 + x)y = 2x^5 - x^4 - 5x^3 + 3x + 1\) $G_{3,3}$ 1
2165.a.270625.1 2165.a \(y^2 + (x^2 + x + 1)y = x^5 + 6x^4 - 4x^3 + x\) $\mathrm{USp}(4)$ 1
2172.a.4344.1 2172.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^3 - 2x^2\) $\mathrm{USp}(4)$ 1
2225.a.11125.1 2225.a \(y^2 + (x^3 + 1)y = -3x^4 + 4x^2 + 2x\) $\mathrm{USp}(4)$ 1
2238.a.13428.1 2238.a \(y^2 + (x + 1)y = -x^5 - x^4 + x^2\) $\mathrm{USp}(4)$ 1
2251.a.2251.2 2251.a \(y^2 + xy = x^5 + x^4 - 2x^3 - x^2 + x\) $\mathrm{USp}(4)$ 1
2326.a.4652.1 2326.a \(y^2 + (x + 1)y = -x^5 + x^4 - x^2\) $\mathrm{USp}(4)$ 1
2348.b.37568.1 2348.b \(y^2 + (x^3 + x + 1)y = x^5 - 4x^4 + 2x^3 - x^2\) $\mathrm{USp}(4)$ 1
2390.a.4780.1 2390.a \(y^2 + (x + 1)y = x^5 + x^4 - 2x^3 - x^2\) $\mathrm{USp}(4)$ 1
2457.a.95823.1 2457.a \(y^2 + (x^3 + 1)y = x^5 - x^4 - 3x^3 + 6x^2 - 6x + 2\) $\mathrm{USp}(4)$ 1
2493.a.7479.1 2493.a \(y^2 + (x^3 + 1)y = -x^4 + 2x^3 - 2x^2 + x\) $\mathrm{USp}(4)$ 1
2564.a.5128.1 2564.a \(y^2 + (x^3 + x + 1)y = -2x^2\) $\mathrm{USp}(4)$ 1
2690.a.26900.1 2690.a \(y^2 + (x^3 + x)y = -2x^4 + 3x^2 - 3x + 1\) $\mathrm{USp}(4)$ 1
2768.a.354304.1 2768.a \(y^2 + y = x^6 - 4x^4 - 5x^3 - 2x^2\) $\mathrm{USp}(4)$ 1
2780.a.5560.1 2780.a \(y^2 + (x^3 + x + 1)y = -x^5 + x^3 + x^2 - 7x + 4\) $\mathrm{USp}(4)$ 1
2836.a.5672.1 2836.a \(y^2 + (x^3 + x + 1)y = x^5 + x^2\) $\mathrm{USp}(4)$ 1
2837.a.2837.2 2837.a \(y^2 + xy = x^5 - x^4 - 2x^3 + x^2 + x\) $\mathrm{USp}(4)$ 1
2859.a.77193.1 2859.a \(y^2 + (x^3 + x + 1)y = 2x^5 + 4x^4 + x^3 + 2x^2\) $\mathrm{USp}(4)$ 1
2873.a.48841.1 2873.a \(y^2 + (x^3 + x + 1)y = 2x^4 + 2x^2 + x\) $\mathrm{USp}(4)$ 1
2900.a.290000.1 2900.a \(y^2 + (x^3 + x)y = -4x^4 + 17x^2 - 29\) $G_{3,3}$ 1
2907.a.8721.1 2907.a \(y^2 + (x^3 + x + 1)y = -x^4 + 2x^3 - 3x^2\) $\mathrm{USp}(4)$ 1
2966.a.5932.1 2966.a \(y^2 + (x + 1)y = x^5 - x^4 - 2x^3 + x^2 + x\) $\mathrm{USp}(4)$ 1
3016.a.6032.1 3016.a \(y^2 + x^3y = -x^4 + 2x^2 - 2x + 1\) $\mathrm{USp}(4)$ 1
3021.a.172197.1 3021.a \(y^2 + (x^3 + 1)y = -x^5 + x^4 - 4x^2 + 2\) $\mathrm{USp}(4)$ 1
Next

Download all search results for